PENGARUH CITRA MEREK DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PENGAMBILAN JASA TRANSPORTASI (STUDI KASUS PADA PO. BEJEU JURUSAN SEMARANG – JAKARTA) - Parmana, Affan Eka; Prihatini, Apriatni Endang (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2017)
The research based on the fact of growing number various alternative transportation services, especially ground transportation. Although bus is still a prima donna for the majority of Indonesian people as an option.The purpose of this research was to find out the influence of brand image andservice quality for user of PO. Bejeu. The population was costumer PO. Bejeu of Semarang-Jakarta. Sample in this research was 100 respondents, which obtained using a purposive sampling technique. Data analysis in this study using SPSS 18.0 for windows, which previously tested the validity, reliability, determination coefficient, correlation coefficient, simple linear regression and multiple linear regression (t-test and F-test) in advance.The results of this research show that brand image and service quality partially or simultaneously affect decisions to use. Quality of Service provide greater influence for decisions on the use than Brand Image. Suggestions can be submitted is brand image of PO. Bejeu needs to be improved again, so that the image of PO. Bejeu as transportation company can be maintained. For example by improvingconvenience of PO. bejeu. In addition, service quality also needs to be improved. Company need to discipline and improve the performance of their employees in order to be more responsive to customers.